Pengaruh Eksternalitas Sampah Plastik Terhadap Kerusakan Ekosistem Pesisir di Sumatera Utara: Penelitian - Ananda Sakinah; Feny Amelia Sinaga; Khairunisa br. Marpaung; Flowrensari Ginting; Adika Sanjaya (Lembaga Penelitian dan Pengabdian Masyarakat, 2025)
Plastic pollution along the coastal areas of North Sumatra has become a serious issue that threatens the sustainability of the environment, economy, and social life of coastal communities. This study aims to understand the negative impacts caused by plastic waste on coastal ecosystems and investigate the underlying factors and resulting consequences. The research employs a qualitative approach through literature review, policy analysis, and data from relevant previous studies. The findings indicate that plastic waste has a direct impact on the degradation of mangrove ecosystems, coral reefs, and various marine species such as fish, sea turtles, and seabirds. The consequences further extend to the economic sector, reflected in declining fish catches and reduced tourist visits in coastal areas. Moreover, the inability of communities and industrial stakeholders to bear the environmental damage costs highlights a significant market failure. Although several government initiatives have been introduced, such as coastal cleanup campaigns and restrictions on single-use plastics in certain areas, their implementation remains fragmented, inconsistent, and lacks integration of external costs. This study emphasizes the need for regulatory and economic-based policies, including extended producer responsibility, stricter limitations on single-use plastics, improved waste management infrastructure, and collaboration among stakeholders to mitigate long-term environmental impacts and enhance the well-being of coastal communities.